1998
DOI: 10.1111/1468-2311.00090
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Time‐Served and Regime on Prisoners' Anticipation of Crime: Female Prisonisation Effects

Abstract: To examine the extent of time-served and regime on incarcerated females, 304 inmates were surveyed about prior lifestyles, violent orientations, and future anticipations of future crime. Results show that women who led a non-violent lifestyle prior to incarceration might, once released, commit crimes of violence largely due to prison experiences through a prisonisation process. A conclusion arising from this finding is that short prison sentences can be as effective a punishment as long prison sentences with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Similar to the experiences of prisoners (Kruttschnitt et al, 2000;Stevens, 1998;Venters et al, 2009;David Scott, 2008;Steel et al, 2004;Goodstein et al, 1984), a lack of response and false promises from the staff reinforced the detainees' conviction that seeking help is futile, which led to a feeling of lack of control and passivity. However, examples such as one detainee succeeding in getting snacks between meals while others fail indicate that with good staff-detainee interaction detainees can attain a sense of control and positively influence their health and well-being in detention.…”
Section: Staff-detainee Interactionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar to the experiences of prisoners (Kruttschnitt et al, 2000;Stevens, 1998;Venters et al, 2009;David Scott, 2008;Steel et al, 2004;Goodstein et al, 1984), a lack of response and false promises from the staff reinforced the detainees' conviction that seeking help is futile, which led to a feeling of lack of control and passivity. However, examples such as one detainee succeeding in getting snacks between meals while others fail indicate that with good staff-detainee interaction detainees can attain a sense of control and positively influence their health and well-being in detention.…”
Section: Staff-detainee Interactionmentioning
confidence: 85%
“…Staff behaviour can make the experience of confinement either bearable or unbearable (Stevens, 1998;Dirkzwager and Kruttschnitt, 2012;Johnsen et al, 2011). Similar to the experiences of prisoners (Kruttschnitt et al, 2000;Stevens, 1998;Venters et al, 2009;David Scott, 2008;Steel et al, 2004;Goodstein et al, 1984), a lack of response and false promises from the staff reinforced the detainees' conviction that seeking help is futile, which led to a feeling of lack of control and passivity.…”
Section: Staff-detainee Interactionmentioning
confidence: 98%
“…In a study surveying 304 female prisoners, Dennis Stevens (1998), found time served in highly authoritarian prisons affected recidivism. Stevens (1998) argues the restrictive model of the prison system stimulates a "culture of violence" within the prison. As Stevens found female prisoners with no history of violence prior to incarceration may commit violent crimes, once released as a response to prisonization.…”
Section: Gang)mentioning
confidence: 99%
“…women were surveyed about their future involvement with crime 81 percent of women reporting an anticipation of future violent crime believed they were incarcerated in a highly authoritarian regime, meaning they were heavily monitored and had a distant relationship with the prison staff. It is these coercive and controlling conditions that Stevens (1998) argues shapes recidivism. The longer the inmate serves in an authoritarian prison system, the more indoctrinated to the prison culture the inmate becomes.…”
Section: Gang)mentioning
confidence: 99%
See 1 more Smart Citation